PENGARUH PEMBERIAN LEGIN, PUPUK NPK (15:15:15) DAN UREA PADA TANAH GAMBUT TERHADAP KANDUNGAN N, P TOTAL PUCUK DAN BINTIL AKAR KEDELAI (Glycine max (L.) Merr.) - Achmad Mulyadi (Kaunia: Integration and Interconnection Islam and Science, 2012)
The aim of this study was to know the effects of legin application, NPK(15;15:15) and urea fertilizer on peat soils on the shoot total N, P content and   nodule development of soybean (Glycine max (L.) Merr.) Factorial Completely Randomized Design (CRD) with five replications were used in this experiment. The first factor was three levels of Rhizobium inoculation (legin), i.e. L0 : without inoculation, L1: 5 g and L2 : 10 g/seed, respectively. The second factor was three levels of NPK fertilizer, i.e. N0 : without NPK, N1 : 0,75 g and N2 : 1,75 g/polybag, respectively. The third factor was three levels of urea fertilizer, i.e. U0  :without urea, U1  : 0,5 g and U2  : urea 1,5 g/polybag, respectively. Plants were grown on 500 g of sterile peat soils added by dolomite and harvested at six weeks after planting. The measured parameters including  effective nodule number and nodule dry weight, shoot total P content and shoot total N content. Collected data were analyzed by Analysis  of Variance (Anova), followed by Duncan’s Multiple Range Test (DMRT) at 5 % level of significant. The result of this experiment showed that legin, NPK and urea fertilizer application could increase effective nodule number, nodule dry weight, shoot total N content and shoot total P content. However, increased fertilizer concertation would decrease effective nodule number, nodule dry weight and shoot total N content but not shoot total P content. Lower NPK or urea fertilizer application was needed for early growth of soybean. NPK fertilizer application gave better growth than urea fertilizer.